2017
DOI: 10.3892/mmr.2017.8006
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑211 suppresses the growth and metastasis of cervical cancer by directly targeting ZEB1

Abstract: Of gynecological cancers, cervical cancer has the second highest incidence globally and is a major cause of cancer‑associated mortality in women. An increasing number of studies have reported that microRNAs (miRNAs) have important roles in cervical cancer carcinogenesis and progression through regulation of various critical protein‑coding genes. The aim of the present study was to investigate the expression and biological roles of miRNA‑211 (miR‑211) in cervical cancer and its underlying molecular mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Therefore, targeting ZEB1 may be an efficient strategy for NPC therapy. Previous studies have also identified that ZEB1 was regulated by various miRNAs in human cancer (39)(40)(41). In a previous study, miR-429 was reported to be downregulated in NPC and to suppress cell migration and invasion through targeting ZEB1 (42).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, targeting ZEB1 may be an efficient strategy for NPC therapy. Previous studies have also identified that ZEB1 was regulated by various miRNAs in human cancer (39)(40)(41). In a previous study, miR-429 was reported to be downregulated in NPC and to suppress cell migration and invasion through targeting ZEB1 (42).…”
Section: Discussionmentioning
confidence: 89%
“…The metastasis of CC was clearly inhibited by miR-3666 and miR-211 through the pituitary tumor-transforming gene 1 ( Pttg1 )/miR-3666/ZEB1 and the miR-211/ZEB1 [124,125] pathways, respectively. Additionally, miR-377 decreases the invasion of CC cells by inversely modulating the expression of ZEB2 [126].…”
Section: The Role Of Emt-related Mirnas In the Metastasis Of CCmentioning
confidence: 99%
“…Additionally, in non-small cell lung cancer, ZEB1, as a target of miR-445, reverses its inhibition of the proliferation, migration and invasion [30]. ZEB1 switches with cervical cancer as a target of several miRNAs, such as miR-211, miR-429 and miR-484 [3133]. In the current study, upregulated expression of ZEB1 was found in cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 58%